Dynamics of bacterial communities across developmental stages of the litchi stink bug, Tessaratoma javanica - Ipsita Samal; Jaipal Singh Choudhary; Ansh Raj; Vinod Kumar; Sunil Kumar; Bikash Das (Scientific Reports)
Abstract The Litchi stink bug, Tessaratoma javanica (Thunberg) (Hemiptera: Tessaratomidae), is a major insect pest of litchi in India. Insect-associated bacteria play significant roles in their growth and development. We studied the bacterial communities linked to T. javanica using 16 S rRNA amplicon sequencing and predicted the functions of associated bacterial communities. The findings revealed that bacterial communities significantly differ across the developmental stages of T. javanica. The primary bacterial phyla across all developmental stages linked to T. javanica were Proteobacteria, Firmicutes, Bacteroidota, Actinobacteria, Patescibacteria, and Nitrospirota. Class Gammaproteobacteria predominated in first and 4th nymphal instars, and adult females, whereas Bacilli dominated the gut of the 3rd, and 5th nymphal instars of T. javanica. Ligilactobacillus apodemi, Staphylococcus xylosus, and Pseudomonas furukawaii were identified as the predominant bacterial species associated with T. javanica. The peak bacterial diversity was observed in the 5th nymphal instar and the lowest in the 1st nymphal instar. The observed changes between growth and developmental stages indicate that bacterial communities are dynamic and perpetually developing to meet the metabolic functions of T. javanica. Comprehending these interactions will improve our understanding of the ecological relationship with this pest and assists in developing and implementing efficient biological control plans for its management.